Stalinism in Poland - Filip Musiał (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2019)
The article presents, in a synthetic manner, the mechanism of introducing the Stalinist system in Poland and describes its essence. It points to the importance of – until now given less value in the relevant literature – the mechanism of elimination of institutions and persons representing the constitutional order and state-creating social fabric, as well as introducing in their place representatives of the lowest social classes and institutions impersonating Polish centres of power, but in fact fully dependent on the USSR. The text focuses on political and social issues, as well as on the extensive repression apparatus.